DEA-Model for Evaluating the Effectiveness of the National Project Implementation “Demography” in the Territory of the Volga Federal District - M. V. Bikeeva; E. A. Sysoeva (Статистика и экономика)
Purpose of the study. From 2018 to 2024 on the territory of the Russian Federation there are national projects in key areas of social policy. In 2025, it is planned to sum up the results of the implementation of these national projects. The presented study focuses on the intermediate results of the national project implementation “Demography”.The purpose of the study is to assess the effectiveness of the national project implementation “Demography” in the Volga Federal District as of 2021.Materials and methods. The methodological basis of the study was the non-parametric method for evaluating the effectiveness of Data Envelopment Analysis (DEA). An input-oriented model was used to increase the inputs without changing the outputs. The target index for the implementation of the national project - the total birth rate - was used as a performance index. Indexes-factors are selected taking into account the possibility of a potential impact on fertility. Among them: general marriage rates; the level of employment of the population of working age; real monetary income of the population; consumer spending on average per capita per month; the number of families who received housing, premises and improved their living conditions during the year.The information base of the study is the data of the Federal State Statistics Service.Results. The regions of the Volga Federal District that are effective and inefficient in terms of achieving the target index for the implementation of the national project “Demography” are identified and their typology is carried out. The group of leading regions close to the implementation of the national project in full includes the Republic of Mari El, the Udmurt Republic and the Orenburg region. They act as benchmarks for other regions of the district in achieving the planned target index for the national project implementation. The group of “hybrid regions”, which includes seven entities, has the ability to ensure the execution of the national project by the end of its implementation period. Four “outsider regions” have the main problems in achieving the targets of the national project “Demography”, including the Republic of Mordovia, with an efficiency coefficient value of 0,742.